-Insensitizing controls for the linear stochastic Korteweg-de Vries equation. Issue 9 (1st September 2016) - Gao, Peng
Abstract : This paper is addressed to showing the existence of -insensitizing controls for the linear stochastic Korteweg–de Vries equation. We solve this problem by reducing the original problem to a controllability problem.